After Pyrrhos - Yuri N. Kuzmin (Karanos, 2024)
The paper examines the relations between the Antigonids and the Aiakids during the forty years after the death of Pyrrhos (272) until the fall of the Molossian monarchy in the late 230s. Alexander II and a few of his successors ruled in Epeiros at that time; Antigonos II Gonatas and his son Demetrios II reigned in Macedonia. The main concerns of this article are a supposed peace treaty between the Antigonids and the Aiakids in 272 (and who signed it from the Epeirote side), the military conflict between Alexander II and the Antigonids during the Chremonidean War, the recognition of the asylia of the Koan Asklepieion by Gonatas and Alexander II as well as by their subjects, and the marriage of Demetrios II to Phthia (its date, especially in the light of the Athenian decrees in honor of the grain-controllers, and the lengthy controversy concerning the identification of the mother of Philip V). Some other topics are also considered.